Darling - Dankworth, John 1927-2010 (Studiocanal, 2015)
"Winner of three Academy Awards and four BAFTA's including Best Actress for Julie Christie, Darling is the story - based on fact - of a goodtime-girl of the era. She's a freelance female who moves from bed to bed on the presumption that fidelity means having only one man in it at a time, and opportunistically bends her ambitions to take advantage of whatever (or whoever) the moment offers her. There are three men in her life, each of whom willingly or involuntarily helps her on her way to the top: Dirk Bogarde plays a TV interviewer, an honest man striving to tell illusion from reality ; Laurence Harvey, an advertising executive, totally cynical about manipulating society's values; and Roland Curram, a gay magazine photographer battening parasitically on glossy society. There is also a 'fourth man' - the one whom Darling marries, only to find herself a prisoner of the smart world she has conquered."
Original: Großbritannien 1965
Extras: trailer
Bildformat 1.66:1
Bestellnummer: 6550824
Keywords: Film; DVD-Video